Combined Use of Trisodium Citrate and Transglutaminase to Enhance the Stiffness and Water-Holding Capacity of Acidified Yak Milk Gels - Lin Yang (Journal of Food Quality)
In this research, the synergistic effect of trisodium citrate (TSC) and microbial transglutaminase (TGase) treatment on the textural properties of acidified yak skim milk gels was investigated. TSC was added to yak skim milk to concentrations of 0, 20, and 40 mmol/L, followed by adjusting the pH to 6.7. The samples were incubated with TGase for the cross-linking reaction, after which the samples were acidified with 1.4% (w/v) gluconodelta-lactone (GDL) at 42°C for 4 h to form gels. The stiffness and water holding capacity (WHC) of gels exhibited higher values at 20 or 40 mmol/L than without TSC. The final storage modulus (G′) of yak milk gels was positively related to the concentration of TSC prior to TGase treatment. Cryoscanning electron microscopy observations showed that the gel networks were more rigid with higher TSC concentrations. Overall, TSC dissociated particles in yak milk into smaller ones. The newly formed particles in yak skim milk could form acid-induced gels with greater stiffness and higher WHC in the presence of TGase.